An Overview of Challenges and Benefits Associated to the Development of Vehicle to Grid Technology - Diaz-Diaz, M; Vidal-Nunez, C (Institute of Electrical and Electronics Engineers Inc., 2021)
The energy stored in Electrical Vehicles can back up the grid during low-generation periods produced by, for instance, unpredictable renewable energy generation. Therefore, Vehicle-to-Grid (V2G) technologies are foreseen as a major player in the energy transition. However, V2G technologies face several barriers: inadequate technology maturity, lack of interoperability, and unknown business models. In this context, this paper aims to describe the main benefits and challenges of V2G technology. Furthermore, a detailed revision is presented regarding EVs charging systems, interoperability protocols and players, and grid integration requirements. © 2021 IEEE.